Da Vinci robot-assisted retroperitoneal tumor resection in 105 patients: a single-center experience - Hao, Qisheng; Cha, Lichao; Zhou, Bin; Li, Xinyu; Gong, Mingkai; Li, Qingze; Dong, Guofei; Song, Mengqi; Wu, Zehua; Guo, Zhongyi; Qiu, Fabo; Wang, Xiaowei; et al. (Frontiers in Oncology, 2024)
Background: The Da Vinci Surgical System (DVSS) has the advantages of minimal invasion, rapid recovery, safety, and reliability. Although the DVSS has been widely used in various abdominal surgeries, descriptions of its use in robot-assisted retroperitoneal tumor resection (RRTR) are limited to case reports; large-sample systematic studies are lacking. The present study was performed to analyze the data of RRTR in our center, summarize our experience, and provide a reference for other retroperitoneal tumor centers. Methods: We retrospectively analyzed the clinical data of 105 patients who underwent RRTR at the Affiliated Hospital of Qingdao University from January 2015 to December 2022. Logistic univariate and multivariate analyses were performed to identify independent risk factors affecting RRTR. A receiver operating characteristic curve was used to find the cut-off value, which was then included in the logistic multivariate analysis for verification.Results: Among the 105 patients, 87 successfully underwent RRTR (DVSS group) and 18 underwent conversion to open surgery (conversion group). There was no significant difference in sex, age, body mass index, history of abdominal surgery, or tumor location between the two groups (P > 0.05). The maximum tumor diameter [odds ratio (OR), 1.041; 95% confidence interval (CI), 1.015-1.067; P = 0.002] and pathological property (OR, 8.646; 95% CI, 2.370-31.544; P = 0.001) were independent risk factors for conversion to open surgery. Further analysis confirmed that the success rate of RRTR was higher for tumors with a maximum diameter of ≤64 mm and benign tumors. Based on our experience and statistical results, we believe that retroperitoneal tumors that meet the following criteria have a higher success rate of DVSS resection: maximum tumor diameter of ≤64 mm, benign tumors, the tumor has relatively clear boundary, no obvious invasion of surrounding tissues and organs, and no need for combined organ resection.Conclusions: RRTR is safe and effective in the treatment of RPT, and the clinical prognosis is similar to that of open surgery. The success rate of RRTR in patients with appropriate surgical indications for this procedure is higher.